ChemInform Abstract: High‐Pressure Transformation in the Cobalt Spinel Ferrites. Issue 8 (February 2015) - Blasco, J.; Subias, G.; Garcia, J.; Popescu, C.; Cuartero, V.
Abstract Pressure‐induced structural changes in CoxFe3‐xO4 (x = 1, 1.5, 1.75) spinels are characterized by high‐pressure angle‐dispersive XRD measurements at room temperature up to 34 GPa.